Complaints against bankers in Ireland on account of the saved capital of Ireland not being lent to a sufficient extent to the farmers and small owners of land in Ireland, considered, and traced to (1) defective state of law as to sheriff's sales; (2) want of local jurisdiction in equity and bankruptcy; (3) want of local map registration of such interests; and (4) the unreformed state of offices of clerk of the peace, sub-sheriff, and sheriff s bailiff, with suggestions for the reform of these offices - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1876)
Complaints against bankers in Ireland on account of the saved capital of Ireland not being lent to a sufficient extent to the farmers and small owners of land in Ireland, considered, and traced to (1) defective state of law as to sheriff's sales; (2) want of local jurisdiction in equity and bankruptcy; (3) want of local map registration of such interests; and (4) the unreformed state of offices of clerk of the peace, sub-sheriff, and sheriff s bailiff, with suggestions for the reform of these offices.
Read before the Society, 21 December 1875
Keywords: Agricultural finance; Banking system; Sheriff's Bailiff; Bankruptcy; 314.15